2013
DOI: 10.1088/0004-6256/145/5/142
|View full text |Cite
|
Sign up to set email alerts
|

Using Photometry to Probe the Circumstellar Environment of Δ Scorpii

Abstract: We acquired Johnson BV photometry of the binary Be disk system δ Scorpii during its 2009, 2010, 2011, and 2012 observing seasons and used it to probe the innermost regions of the disk. We found that several disk building events have occurred during this time, resulting in an overall brightening in the V band and reddening of the system. In addition to these long-term trends, we found cyclical variability in each observing season on timescales between 60 and 100 days. We were able to reproduce the changes in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…We take the Galactocentric cylindrical coordinate system (R, Φ, Z) to characterize the Galactic dust distribution, where R is the Galactocentric radius, Φ is the position angle and Z is the vertical distance. We assume that the dust distribution is axisymmetric and can be parameterized by an exponential disk (Misiriotis et al 2006;Jones et al 2011)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We take the Galactocentric cylindrical coordinate system (R, Φ, Z) to characterize the Galactic dust distribution, where R is the Galactocentric radius, Φ is the position angle and Z is the vertical distance. We assume that the dust distribution is axisymmetric and can be parameterized by an exponential disk (Misiriotis et al 2006;Jones et al 2011)…”
Section: Methodsmentioning
confidence: 99%
“…For the stellar thin disk, the general conclusion is that it can be fitted by an exponential disk with scale-length 2.6 ± 0.5 kpc and scale-height 220 ∼ 450 pc. For the dust component, it has been shown that, despite of spiral arms, flares and warps (Drimmel & Spergel 2001;Marshall et al 2006;Amôres & Lépine 2005;Reylé et al 2009), the global distribution of dust also follows an exponential disk (Misiriotis et al 2006;Jones et al 2011). However, the scale-length and scale-height of the dust disk have not been constrained very well yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can partially explain the observed scatter. In addition, the dust scale height is 120 pc (Jones et al 2011). First, this can explain the large differential reddening within the bulge.…”
Section: Far Disk Source?mentioning
confidence: 97%
“…These corrections rely on column densities calculated from 100 and 240 µm Galactic emission along the line-of-sight out to infinity, and therefore may overestimate the true extinction to nearby stars. Jones et al (2011) provides a more robust Galactic extinction map by fitting extinction curves to the fluxes of ∼56,000 M dwarfs in the spectral range 5700-9200Å from the W11 catalog. We correct for extinction using the method of Jones et al (2011), except for M dwarfs not present in the Jones et al (2011) catalog, where we apply the extinction corrections of Schlegel et al (1998).…”
Section: Initial Samplementioning
confidence: 99%